2017
DOI: 10.21833/ijaas.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Market sensing, innovation capability and market performance: The moderating role of internal information dissemination

Abstract: Market sensing and internal information dissemination are popular concepts in the field of marketing and strategic management. Scholars in these fields are appreciating the roles of market sensing and internal information dissemination in understanding the business environmental changes to sustain competitive advantages for better firm performance. However, the interaction of market sensing and internal information dissemination couched within complementarity prospective to some extend has not been empirically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Process innovation capability refers to strategies for rebuilding innovation and company activities in product creation. Innovation capability improves the company's processes and performance because it updates its activities and market achievements (Ahmed, Ibrahim, & Hasaballah, 2017).…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…Process innovation capability refers to strategies for rebuilding innovation and company activities in product creation. Innovation capability improves the company's processes and performance because it updates its activities and market achievements (Ahmed, Ibrahim, & Hasaballah, 2017).…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…Process innovation capability refers to strategies for rebuilding innovation and company activities in product creation. Innovation capability improves the company's processes and performance because it updates its activities and market achievements (Ahmed, Ibrahim, & Hasaballah, 2017).…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…Market sensing refers to a company's ability to anticipate market changes and detect market opportunities on the basis of information from its business ecosystem (Mu, 2015). Market sensing is to obtain information about customers, competitors and changes in the business environment obtained through market intelligence through sense, sensemaking and response in order to take appropriate action (Ahmed et al, 2017).…”
Section: Market Sensing Capabilitymentioning
confidence: 99%
“…Market sensing that is developed by seeking information and responding to changes in the market environment quickly can improve marketing performance (Vorhies & Morgan, 2005). Previous studies showed that marketing performance can be developed when companies are able to understand environmental changes, understand competitors' strategies and respond quickly to changes in customer needs (Ahmed et al, 2017;Hendar et al, 2020) H3: There is a positive relationship between MSC and MP…”
Section: Digital Marketing Capability and Value Creation Ambidexteritymentioning
confidence: 99%